1999
DOI: 10.1177/030089169908500108
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Synthase (Fas) Predictive Strength in Poorly Differentiated Early Breast Carcinomas

Abstract: FAS is a reliable prognosticator of recurrence in poorly differentiated early breast carcinomas. Association of FAS with PLVI may be useful to plan a correct follow-up in patients with breast neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(33 citation statements)
references
References 31 publications
0
32
0
1
Order By: Relevance
“…In one of these, there was a 9-fold increased risk of death when high levels of FAS expression occurred together with a high proliferative index (>17%). 54,55 A total of 17 cytoskeletal-associated proteins with diverse biological functions were significantly up-regulated in ERα+ breast tumors (Suppl. Table S7a).…”
Section: Discussionmentioning
confidence: 99%
“…In one of these, there was a 9-fold increased risk of death when high levels of FAS expression occurred together with a high proliferative index (>17%). 54,55 A total of 17 cytoskeletal-associated proteins with diverse biological functions were significantly up-regulated in ERα+ breast tumors (Suppl. Table S7a).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was done as described previously (12)(13)(14). Briefl y, cell lysates were separated by SDS-polyacrylamide gel electrophoresis followed by transfer to a PVDF membrane.…”
Section: Cell Lysate Preparation and Western Blot Analysismentioning
confidence: 99%
“…Overexpression of FASN has been associated with poor prognosis and higher risk of recurrence of human cancers of the breast (9)(10)(11)(12) and prostate ( 13 ), as well as many other types of cancers ( 1 ), suggesting that increased FASN expression may also contribute to disease progression and treatment failure. In particular, FASN overexpression has been found in a drug-selected breast cancer cell line, and this elevation contributes to cellular resistance to Adriamycin (doxorubicin) and mitoxantrone in breast ( 14 ) and to gemcitabine in pancreatic cancer cells ( 15 ).…”
mentioning
confidence: 99%
“…In addition to affecting adipogenesis, fatty acids produced by FAS are known to stimulate other signaling pathways, including autophagy and miRNA signaling ( 63,64 ). FAS has also received much attention regarding the regulation of its activity during cancer development (19)(20)(21)(22)(23). As a key enzyme regulating energy metabolism and as a metabolic oncogene, FAS has been considered as a potential target for the development of antiobesity and anti-cancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…
reported that FAS is involved in the regulation of adipose tissue mass ( 1, 10-18 ), a key enzyme regulating energy metabolism, and a metabolic oncogene ( 19,20 ). Therefore, FAS has been considered as a potential target for the development of anti-obesity and anti-cancer drugs (21)(22)(23)(24)(25).
…”
mentioning
confidence: 99%